SKENARIO MASA DEPAN UNTUK SEKTOR PUBLIK DAN PENGARUHNYA TERHADAP PEGAWAI NEGERI SIPIL - Yogantara Setya Dharmawan (JURNAL TEKNOLOGIA, 2018)
Future scenario planning for public services and their impact on civil servants aims to give an idea of ​​how public services will look like in the next 20 to 30 years. Future scenarios are developed based on improvement of the application of information technology to improve public services' quality. Then, the future scenario planning that developed for public services is expected to provide an overview of the government how future will occur, especially its impact on civil servants. Thus, the government will be able to determine the right strategy to address the scenarios that will occur. Future Scenarios are developed using Scenario Planning method by applying 7 steps of future scenario development. Then, three possible scenarios were selected and analyzed to identify the impact including solution proposals using McKinsey 7s analysis. The results of this paper show the 3 most likely scenarios relating to future public services and their impact on civil servants and then one of the most relevant scenario is selected using the justification matrix for impact analysis and solution proposals using 7s McKinsey.